2019
DOI: 10.1021/acs.analchem.8b04829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multisialylated LacdiNAc Structures as Highly Prostate Cancer Specific Glycan Signatures on PSA

Abstract: Serum prostate-specific antigen (PSA) test is the current gold standard for screening and diagnosis of prostate cancer (PCa), while overdiagnosis and overtreatment are social problems. In order to improve the specificity and exclude a false positive diagnosis in PSA test, PCa-specific glycosylation subtypes of PSA were explored using in-depth quantitative profiling of PSA glycoforms based on mass spectrometric oxonium ion monitoring technology. As a result of analysis using sera from 15 PCa or 15 benign prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…We previously identified PSA with tri-antennary glycan in prostate cancer serum by MALDI-MS 38 . Haga et al 39 analysed glycan structures of PSA using LC-MS/MS and their data showed that multi-antennary glycans are present in greater amounts in the sera of prostate cancer patients compared with BPH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously identified PSA with tri-antennary glycan in prostate cancer serum by MALDI-MS 38 . Haga et al 39 analysed glycan structures of PSA using LC-MS/MS and their data showed that multi-antennary glycans are present in greater amounts in the sera of prostate cancer patients compared with BPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done which focus glycans as biomarkers in prostate cancer 3 , especially N-glycan alterations of PSA [9][10][11][12]39,43,44 . Previous studies have revealed that not all patients can be detected by measuring the increase focusing only on a specific glycan structure such as α2,3-sialyl or LacdiNAc residues [9][10][11][12]43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of glycans is oen associated with various human diseases, such as prostate cancer and colorectal cancer. [5][6][7][8][9] Therefore, the analysis of glycans can offer insight into glycosylation functions and contribute to diagnosis and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is the leading cancer in males from which the mortality rate is increasing . Early diagnosis of this disease is needed for therapy.…”
Section: Sers‐based Biosensorsmentioning
confidence: 99%
“…Prostate cancer is the leadingc ancer in males from which the mortality rate is increasing. [120] Early diagnosis of this disease is neededf or therapy. Prostate cancera ntigen 3( PCA3) is expressed rapidly in prostate tissue during this disease.…”
Section: Gold Nps As Asers Biosensormentioning
confidence: 99%